Oxidative and nitrosative stress during pulmonary ischemia-reperfusion injury: from the lab to the OR - Gielis, Jan F.; Beckers, Paul A. J.; Briedé, Jacco J.; Cos, Paul; Van Schil, Paul Ey (Annals of Translational Medicine; Vol 5, No 6 (March 28, 2017): Annals of Translational Medicine, 2017)
Oxidative and nitrosative stress are an umbrella term for pathophysiological processes that involve free radical generation during inflammation. In this review, the involvement of reactive oxygen and nitrogen species is evaluated during lung ischemia-reperfusion injury (LIRI) from a surgical point of view. The main biochemical and cellular mechanisms behind free radical generation are discussed, together with surgical procedures that may cause reperfusion injury. Finally, different therapeutic strategies are further explored. A literature search was performed, searching for “lung ischemia reperfusion injury”, “reperfusion injury”, “large animal model” and different search terms for each section: “surgery”, “treatment”, “cellular mechanism”, or “enzyme”. Although reperfusion injury is not an uncommon entity and there is a lot of evidence concerning myocardial ischemia-reperfusion injury, in the lung this phenomenon is less extensively described and studies in large animals are not easy to come by. With increasing number of patients on waiting lists for lung transplant, awareness for this entity should all but rise.